Role of Knowledge Sharing and Organizational Commitment to Development Micro Small and Medium Enterprises (MSMEs) - Sri Maria Ulfha; MLN. Rosmadi; Endah Widiastuti K; M. Irsyad Raspati (Budapest International Research and Critics University, 2019)
This study aims to determine the extent of the role of sharing knowledge and organizational commitment in developing MSMEs. The research method used is a qualitative method with a descriptive verification approach. From the results of the research conducted, it is obtained data that the sharing of knowledge and commitment of well-managed organizations by management is very beneficial for increasing employee innovation and creativity to produce quality and competitive products in both domestic and international markets. This is if done consistently will have an impact on the development of MSMEs, which in turn can improve employee welfare.